1993
DOI: 10.1002/app.1993.070470912
|View full text |Cite
|
Sign up to set email alerts
|

Alginate polyelectrolyte ionotropic gels. VI. Novel synthesis of diketoalginates as biopolymer precursors

Abstract: SYNOPSIS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 16 publications
4
16
0
Order By: Relevance
“…Therefore, all present experimental runs were performed under the conditions of [PEC] 0 < 10 −2 mol dm −3 . Similar behavior was observed in some redox reactions involving pectin polysaccharide as a reducing agent …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Therefore, all present experimental runs were performed under the conditions of [PEC] 0 < 10 −2 mol dm −3 . Similar behavior was observed in some redox reactions involving pectin polysaccharide as a reducing agent …”
Section: Resultssupporting
confidence: 80%
“…[Fe(CN) 6 ] 3− = 7 × 10 −4 , [OH − ] = 3 × 10 −2 , I = 0.1 mol dm −3 at 40 • C oxidation rates. Therefore, all present experimental runs were performed under the conditions of [PEC] 0 < 10 −2 mol dm −3 .Similar behavior was observed in some redox reactions involving pectin polysaccharide as a reducing agent 22,23,37,38.…”
supporting
confidence: 57%
“…Although, permanganate ion is a strong oxidizing agent which has been widely used for oxidation of most organic and inorganic compounds (Stewart, 1965;Lee, 1980;Fatiadi, 1987;Dash, Patel, & Mishra, 2009), a little attention has been focused to the oxidation of macromolecules by this oxidant. Eventhough, the kinetics of permanganate oxidation of some carbohydrates containing secondary alcoholic groups such as alginates (Hassan, 1993), pectates (Khairou & Hassan, 2000;Khairou, 2003;Abdel-Mohsen & Nassr, 2010), carboxymethyl cellulose (Shaker, 2001) and methyl cellulose (El-Khatib, 2002;Shaker, El-Khatib, & Mahran, 2007) in alkaline solution has been studied by us for the first time. Unfortunately, the oxidation of sulfated carbohydrates has received a little attention .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this work also aims at shedding light on the nature of these short-lived transient species and the aqueous chemistry of carrageenan macromolecule as well as extending our investigation on the oxidation of carbohydrate macromolecules. [9][10][11][12][13] Preliminary experiments indicated that the oxidation of K-carrageenan by alkaline permanganate proceeded via detectable intermediate complexes and the rates of formation and decomposition were of such magnitude that they could be monitored using a conventional spectrophotometer. The initial step was found to be fast involving the formation of complexes, followed by a slower step corresponding to the decomposition of these complexes at the final stage of the reaction to give rise to the products.…”
mentioning
confidence: 99%
“…Hence, the stoichiometric reaction can be represented by the following equation:ðC 12 H 17 O 12 SÞ n À þ 2MnO 4 À þ 1=2O 2 ¼ ðC 12 H 11 O 13 SÞ n À þ 2MnO 2 þ 2OH À þ 2H 2 Oð3Þwhere ðC 12 H 17 O 12 SÞ n À and ðC 12 H 11 O 13 SÞ n À are K-carrageenan and its keto-acid oxidation product, respectively. The oxidation product of K-carrageenan was identified by IR spectroscopy and chemical analysis as described elsewhere 11. 13 Na---O-Mn VI O 3 Na---O-Mn VI O 3 Na---O-Mn VI O 3…”
mentioning
confidence: 99%